2007
DOI: 10.1016/j.amjhyper.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial Correlations of Carotid Intima–Media Thickness and Flow-Mediated Dilation in a Siberian Population

Abstract: Our findings confirm that a substantial proportion of the variability of carotid IMT and brachial FMD is attributable to genetic variation. They also suggest that offspring share more genetic or environmental determinants of FMD with fathers than their mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In recent years, the weight of inherited factors on carotid IMT (“heritability”) has been investigated in general population samples of different ethnicities1315 or in selected samples of individuals with a family history of different cardiovascular diseases 1620. Wang et al 18 demonstrated, in a multivariate-adjusted model, a heritability of 40% for carotid IMT in adult offspring of patients with a history of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the weight of inherited factors on carotid IMT (“heritability”) has been investigated in general population samples of different ethnicities1315 or in selected samples of individuals with a family history of different cardiovascular diseases 1620. Wang et al 18 demonstrated, in a multivariate-adjusted model, a heritability of 40% for carotid IMT in adult offspring of patients with a history of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…20 In the analysis, we used the mean IMT estimate from either the right or the left artery, whichever was higher. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, twin and family studies suggest endothelial function or FMD is a heritable trait. A significant familial aggregation was reported for FMD measured in 81 nuclear families with a heritability estimate of 0.58 for FMD in sibling pairs (Ryabikov et al, 2007). The Northern Manhattan Family Study reported heritability for FMD of 0.17 in Hispanic Caucasians after adjusting for age, sex, and cardiovascular disease (CVD) risk factors (Suzuki et al, 2008).…”
Section: Genetic Regulation Of Endothelial Function In Humansmentioning
confidence: 99%